Mersilene Tape Thiersch Operation for Rectal Prolapse in Frail Elderly: A Case Series - Itekena Eugene Wakama (INTERNATIONAL JOURNAL OF HEALTH AND PHARMACEUTICAL RESEARCH, 2026)
Background: Full-thickness rectal prolapse in frail elderly patients is challenging. The Thiersch operation using an encircling tape is minimally invasive, but data on Mersilene tape in patients with small prolapse (≤5 cm) and varying frailty are limited. This case series evaluates outcomes of a Thiersch procedure under regional anesthesia, with a focus on cost-effectiveness and relevance to low- and middle-income countries (LMICs). Methods: Twelve consecutive patients (9 females, 3 males, age 68–93 years) with full-thickness rectal prolapse ≤5 cm underwent a Thiersch operation with Mersilene tape under spinal anaesthesia. Baseline frailty (Clinical Frailty Scale 1–5)24, comorbidities, constipation type (PAC SYM)25, and anal sphincter weakness were recorded. Outcomes at 1 year included prolapse recurrence, complications, and mortality. A cost-effectiveness analysis compared Mersilene tape to alternative synthetic materials. Results: Median age 77.5 years; median prolapse length 3.4 cm. Frailty ranged from robust (N=1) to terminally frail (N=2). Mean operative time was 55.0 minutes (range 43–62). At 1 year, 7 patients (58.3%) had complete follow-up; 2 died (16.7%), and 3 were lost (25%). Among the followed patients, prolapse recurrence occurred in 1 (14.3%). Constipation improved in all 4 constipated patients who completed follow-up. Complications occurred in 5 patients (41.7%): UTI (1), surgical site infection (1), temporary constipation (1), pneumonia (1 fatal), sepsis with fatal outcome (1), and delirium/pneumonia (1, later LTFU). No tape erosion or faecal impaction occurred. Conclusion: The Mersilene tape Thiersch operation under regional anaesthesia is feasible in frail elderly with small rectal prolapse. Recurrence rates are acceptable. The procedure offers a favourable cost-effectiveness profile, particularly valuable in resource-limited healthcare settings.